Interpretative phenomenological analysis of the experiences of single Filipino women - Reyes-Laureano, Rachel C. (Quezon City Psychological Association of the Philippines, 2012)
This study used Interpretative Phenomenological Analysis (IPA) to examine the lived experience of singleness of ten Filipino women. The women were interviewed three times and two types of data were gathered in order to understand their singleness in depth: life histories and phenomenology.
Keywords: Singleness; Single Females; Phenomenology; Life Histories